PENYEWAAN ONLINE WEDDING ORGANIZER BERBASIS WEB - Maiyana, Efmi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Wedding organizers help prospective brides and families in the planning and implementation of a series of wedding events in accordance with the schedule and budget that has been set by offering various concepts of marriage but prospective brides have difficulty knowing the WO is constrained by a number of things such as lack of information, difficulties in ordering and takes time to visit WO places. Constraints The website is a forum for wedding organizer promotions to brides that can be accessed at any time where the system is designed using the PHP programming language and MySQL database. The aim of the research is to design a web-based Wedding Organizer (W0) information system so that prospective brides can find wedding concepts desired is adjusted based on the number of invitations, finance, catering, buildings, and bridal aisle decorations while for service providers is the promotional media WO has so that it runs a wedding organizer business process that connects service providers with consumers through electronic transactions using the internet.